IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING PROCEDURE TEXTS BY USING VIDEOS - Widya Ladeci Simbolon; Amrin Saragih (Universitas Negeri Medan, 2013)
This study deals with the students’ achievement improvement in writing procedure texts by using videos by applying classroom action research. The subjects of this research were 38 students of class X-1 SMA TELADAN MEDAN. After analyzing the data in two cycles of classroom action research, it was found there was an improvement of students’ mean score from 60.44 in assessment before applying video became 68.52 in cycle I and improved again became 78.89 in cycle II. It means that the use of video significantly improves the students’ achievement in writing procedure texts. Keywords: writing, procedure text, action research, videos, X-I SMA Teladan Medan.